2021
DOI: 10.18657/yonveek.838461
|View full text |Cite
|
Sign up to set email alerts
|

The Relation of Public Expenditures with Economic Growth in OECD Countries

Abstract: Many empirical studies have been conducted to analyse the relationship between public spending and economic growth. In the literature review for the analysis of this relationship, the studies are concentrated around Keynes and Wagner Hypothesis. Wagner argues that this relationship is from economic growth to public expenditures while Keynes argues that it is from public expenditures to economic growth. In this study, Keynes's hypothesis is examined through the use ofthe variables of economic growth, public exp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 34 publications
0
3
0
Order By: Relevance
“…This shows that government spending has an effect on economic growth. Both public spending and inflation were found to have a beneficial influence on short-term economic growth (Ertekin & Bulut, 2021). Srinivasan (2013) discovered a direct relationship between public spending and economic growth from 1973 to 2012, demonstrating that total public spending has a positive impact on economic growth, which Simiyu (2015) supported by evaluating the correlation of public spending and economic growth using the Granger causality test.…”
Section: Development Of Hypothesesmentioning
confidence: 99%
See 1 more Smart Citation
“…This shows that government spending has an effect on economic growth. Both public spending and inflation were found to have a beneficial influence on short-term economic growth (Ertekin & Bulut, 2021). Srinivasan (2013) discovered a direct relationship between public spending and economic growth from 1973 to 2012, demonstrating that total public spending has a positive impact on economic growth, which Simiyu (2015) supported by evaluating the correlation of public spending and economic growth using the Granger causality test.…”
Section: Development Of Hypothesesmentioning
confidence: 99%
“…The findings of these models enable the use of dynamic data for comparison study over multiple periods and years, with implications for the economy and other areas. The use of the Ordinary Least Squares (OLS) econometric model allows for the control of factors that are fundamentally difficult to assess using traditional and simpler methods (Ertekin & Bulut, 2021).…”
Section: Modelmentioning
confidence: 99%
“…Olanrewaju and Funlayo [77] concluded that as well as Wagner's Law is valid in some countries in the panel, Keynes Hypothesis is valid in other countries also. Wu et al [78], Altıner [13], Altınok and Arslan [79], Sagdic et al [80], Nusair and Olson [3], and Ertekin and Bulut [81], who uses panel data analysis in their studies, had reached findings in favour of both approaches. However, Kuckuck [82] reached contrasting results in his research.…”
Section: Selected Literaturementioning
confidence: 99%